Validity of the MarkWiiR for kinematic analysis during walking and running gaits - Padulo, Johnny; Vando, Stefano; Chamari, Karim; Chaouachi, Anis; Bagno, Davide; Pizzolato, Fabio (Biology of Sport, 2015)
The aim of this study was to validate the MarkWiiR (MW) captured by the Nintendo Wii-Remote (100-Hz) to assess active marker displacement by comparison with 2D video analysis. Ten participants were tested on a treadmill at different walking (1<6 km · h-1) and running (10<13 km · h-1) speeds. During the test, the active marker for MW and a passive marker for video analysis were recorded simultaneously with the two devices. The displacement of the marker on the two axes (x-y) was computed using two different programs, Kinovea 0.8.15 and CoreMeter, for the camera and MW, respectively. Pearson correlation was acceptable (x-axis r≥0.734 and y-axis r≥0.684), and Bland–Altman plots of the walking speeds showed an average error of 0.24±0.52% and 1.5±0.91% for the x- and y-axis, respectively. The difference of running speeds showed average errors of 0.67±0.33% and 1.26±0.33% for the x- and y-axes, respectively. These results demonstrate that the two measures are similar from both the x- and the y-axis perspective. In conclusion, these findings suggest that the MarkWiiR is a valid and reliable tool to assess the kinematics of an active marker during walking and running gaits.